Combination COX-2 inhibitor and metformin attenuate rate of joint replacement in osteoarthritis with diabetes: A nationwide, retrospective, matched-cohort study in Taiwan - Lu, Chieh-Hua; Chung, Chi-Hsiang; Lee, Chien-Hsing; Hsieh, Chang-Hsun; Hung, Yi-Jen; Lin, Fu-Huang; Tsao, Chang-Huei; Hsieh, Po-Shiuan; Chien, Wu-Chien (PloS one, 2018)
Osteoarthritis (OA) is the most common form of arthritis associated with an increased prevalence of type 2 diabetes mellitus (T2DM), however their impact on decreasing joint replacement surgery has yet to be elucidated. This study aimed to investigate if the combination of COX-2 inhibitor and metformin therapy in OA with T2DM were associated with lower the rate of joint replacement surgery than COX-2 inhibitor alone. In total, 968 subjects with OA and T2DM under COX-2 inhibitor and metformin therapy (case group) between 1 January to 31 December 2000 were selected from the National Health Insurance Research Database of Taiwan, along with 1936 patients were the 1:2 gender-, age-, and index year-controls matched without metformin therapy (control group) in this study. Cox proportional hazards analysis was used to compare the rate of receiving joint replacement surgery during 10 years of follow-up. At the end of follow-up, 438 of all enrolled subjects (15.08%) had received the joint replacement surgery, including 124 in the case group (12.81%) and 314 in the control group (16.22%). The case group tended to be associated with lower rate of receiving the joint replacement surgery at the end of follow-up than the control group (p = 0.003). Cox proportional hazards regression (HR) analysis revealed that study subjects under combination therapy with metformin had lower rate of joint replacement surgery (adjusted HR 0.742 (95% CI = 0.601-0.915, p = 0.005)). In the subgroups, study subjects in the combination metformin therapy who were female, good adherence (>80%), lived in the highest urbanization levels of residence, treatment in the hospital center and lower monthly insurance premiums were associated with a lower risk of joint replacement surgery than those without. Patients who have OA and T2DM receiving combination COX-2 inhibitors and metformin therapy associated with lower joint replacement surgery rates than those without and this may be attributable to combination therapy much more decrease pro-inflammatory factors associated than those without metformin therapy.